THE ROLE OF SPORTS IN PROMOTING A HEALTHY LIFESTYLE - Raghuram, Raicherla; Yugandhar, Dasari; Parchuri, Gopi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the multifaceted relationship between sports and overall well-being, emphasizing its significance, challenges, and potential benefits. Sports participation is widely recognized as a cornerstone of physical fitness, mental resilience, and an enhanced quality of life. Through a structured research approach, this study examines key findings that deepen our understanding of how sports contribute to a healthier lifestyle. The research highlights the positive effects of regular sports engagement on physical health, psychological well-being, and social integration, offering valuable insights for future research and public health policies.